Brand Ambassador and Brand Personality on Decision to Purchase Nature Republic in Karawang - Pebriyanti, Evi; Kusmayadi, Odang (Pandawan, 2022)
Cosmetics have become a necessity for society, especially women. The country that is currently famous for its cosmetic products is South Korea. The famous Korean cosmetic product in Indonesia is Nature Republic. In 2019, Nature republic's sales experienced a very drastic decline. Strategies that can be used to increase sales are Brand Ambassador and Brand Personality. The method used in this research is quantitative research methods. This research uses descriptive research with a quantitative approach. A sample of 270 respondents. The sampling technique used was stratifed sampling. The results showed that Brand Ambassador and Brand Personality had a strong enough correlation, namely 48.8%, partially Brand Ambassador to purchasing decisions had an effect of 7.6%, partially Brand Personality on purchasing decisions had an effect of 54.9% and simultaneously Brand Ambassador and Brand Personality for Purchase Decision by 62.5%. Meanwhile, 37.5% was influenced by other variables which were not researched. There is a Partial Influence of Brand Personality (X2) on Purchase Decisions (Y) for Korean Nature Republic Cosmetics Users in Karawang Regency of 0.549 or 54.9%. This shows that Brand Personality (X2) contributes or has a positive effect on Purchasing Decisions (Y). The simultaneous influence of Brand Ambassador (X1) and Brand Personality (X2) on Purchase Decisions (Y) of Korean Nature Republic Cosmetics Users in Karawang Regency is 0.625 or 62%, while the remaining 37.5% is influenced by variables not studied. This shows that Brand Ambassador (X1) and Brand Personality (X2) together have an influence on the Company's Purchasing Decision (Y). Korean Cosmetics User Nature Republic in Karawang Regency.